1960
DOI: 10.2151/jmsj1923.38.5_213
|View full text |Cite
|
Sign up to set email alerts
|

On the Ice-nucleating Ability of Rock-forming Minerals and Soil Particles&lowast

Abstract: The ice-nucleating abilities of various rock-forming minerals which exist commonly on the surface of the earth were determined in laboratory.The most effective minerals as ice nuclei among the minerals tested are magnetite, hypersthene, kaolinite and sanidine.Quartz, amphibole, olivine, calcite and orthoclase are found to be less effective.As for the volcanic ejecta, the degree of weathering to which they have been subjected seems to give significant effect on their ice-nucleating abilities. The temperature sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
1

Year Published

1963
1963
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 15 publications
5
45
1
Order By: Relevance
“…More effective nucleation scavenging of hygroscopic particles containing SO42 at lower altitudes in the form of CCN would limit their ability to reach higher altitudes where deeper clouds produce snow. At those higher altitudes, dust particles can serve as effective IN (Isono and Ikebe, 1960; Kumai, 1961; Twohy and Gandrud, 1998; Heintzenberg et al, 1996; DeMott et al, 2003a, b; Sassen et al, 2003; Czizco et al, 2004; Koehler et al, 2007; Prenni et al, 2007; Zimmermann et al, 2008), and as noted already, they contain enhanced levels of NO3 due to reactions with HNO 3 (e.g. Malm et al, 2004; Lee et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…More effective nucleation scavenging of hygroscopic particles containing SO42 at lower altitudes in the form of CCN would limit their ability to reach higher altitudes where deeper clouds produce snow. At those higher altitudes, dust particles can serve as effective IN (Isono and Ikebe, 1960; Kumai, 1961; Twohy and Gandrud, 1998; Heintzenberg et al, 1996; DeMott et al, 2003a, b; Sassen et al, 2003; Czizco et al, 2004; Koehler et al, 2007; Prenni et al, 2007; Zimmermann et al, 2008), and as noted already, they contain enhanced levels of NO3 due to reactions with HNO 3 (e.g. Malm et al, 2004; Lee et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…Hutchings et al (2009) focused on monsoon clouds near Flagstaff, Arizona and suggested that windblown soils serve as CCN and can be found in cloud water. It is widely accepted that dust particles act as both CCN (Levin et al, 1996; Rosenfeld et al, 2001; Koehler et al, 2007) and IN (Isono and Ikebe, 1960; Kumai, 1961; Twohy and Gandrud, 1998; Heintzenberg et al, 1996; DeMott et al, 2003a, b; Sassen et al, 2003; Cziczo et al, 2004; Koehler et al, 2007; Prenni et al, 2009; Zimmermann et al, 2008), which is important for the Southwest as it has the highest dust concentrations in the United States (e.g. Malm et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Isono and Ibeke (1960) and Pinti et al (2012) show that kaolinites, montmorillonites and illites from different sources can have different physical and chemical properties. Zimmermann et al (2008) point out that the chemical composition of minerals, in particular of montmorillonite and illite, can be highly variable.…”
Section: Comparison Of Different Mineralsmentioning
confidence: 99%
“…Several laboratory studies have confirmed that soil dusts may include much more efficient INPs than desert dusts and clay minerals [Isono and Ikebe, 1960;Fornea et al, 2009;Conen et al, 2011;O'Sullivan et al, 2014;Tobo et al, 2014]. Therefore, soil dusts may initiate the formation of ice in droplet and mixed-phase clouds.…”
Section: Introductionmentioning
confidence: 99%